Anak Sebagai Pelaku Kecelakaan Lalu Lintas Yang Menyebabkan Kematian (Studi Kasus Polres Bone Bolango) - Angraini K. Baculu; Fence M. Wantu; Julisa Aprilia Kaluku (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of the research is to analyze the factors that cause criminal acts of traffic accidents committed by children and the responsibility of children related to traffic accidents committed by minors which cause death. The research method used in this research is an empirical method. The results of the research show that: 1. The factors causing the occurrence of criminal traffic accidents committed by children which cause death are. General factors include: Manuia, Weather/Nature, Road Conditions. Then external factors, including: Age, personal existence, lack of awareness of the safety of oneself and others, lack of awareness of traffic regulations. And internal factors, including: Lack of parental attention, social environment.2. Responsibility of children for criminal acts of traffic accidents by minors which cause death. The provisions for criminal fines for children whose negligence causes someone to lose their life in Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation can be imposed a fine that can be imposed on childrezn whose negligence causes someone to lose their life at most ½ (one half) of the maximum threat of imprisonment for adults. It can be concluded that for children whose negligence is proven to result in someone losing their life, the threat of imprisonment that can be imposed on them is ½ of the fine in Law Number 22 of 2009 concerning Road Traffic and Transportation. Because the criminal fine in Law Number 22 of 2009 concerning Road Traffic and Transportation is a maximum of IDR 12,000,000.00 (twelve million rupiah), then for a child whose negligence causes someone to lose their life a maximum of IDR 6,000,000, 00 (six million rupiah). Keywords: Accident; Traffic; Child; death.